Förekomst av B- och T-lymfocyter i hypofysen hos hund - Blomqvist, Marcus (SLU/Dept. of Clinical Sciences (until 231231), 2018)
The pituitary gland, or hypophysis, is often referred to as the ”master gland”. It controls the production and secretion of hormones by peripheral endocrine glands. The pituitary gland is situated ventral to the hypothalamus in the hypophyseal fossa.